Dangerous Love : Sex Work, Drug Use, and the Pursuit of Intimacy in Tijuana, Mexico. - Syvertsen, Jennifer Leigh. (University of California Press, 2022)
A free open access ebook is available upon publication. Learn more at www.luminosoa.org. The relationships between female sex workers and their noncommercial male partners are often assumed to be coercive and anchored in risk, dismissed as "pimp-prostitute" arrangements by researchers and the general public alike. Yet, these stereotypes unjustly erase the complexity of lives we imagine to be consumed by social suffering. Dangerous Love centers a framework of love to rethink sex workers' intimate relationships as commitments to collective solidarity and survival in contexts of oppression. Combining epidemiological research and ethnographic fieldwork in Tijuana, Mexico, Jennifer Leigh Syvertsen examines how individuals try to find love and meaning in lives marked by structural violence, social marginalization, drug addiction, and HIV/AIDS. Linking the political economy of inequalities along the border with emotional lived experience, this book explores how intimate relationships become dangerous safe havens that fundamentally shape both partners' well-being. Through these stories, we are urged to reimagine the socially transformative power of love to carve new pathways to health equity.